Bacterial community changes and their responses to nitrogen addition among different alpine grassland types at the eastern edge of Qinghai–Tibetan Plateau - Qi, Xing-e; Wang, Chen; He, Tianjiao; Ding, Fan; Zhang, Xinfang; An, Lizhe; Xu, Shijian (Archives of microbiology, 2021)
Soil microbes play a fundamental role in maintaining nutrient biogeochemical cycles. To understand the distribution of soil bacterial communities on grassland plateaus, high-throughput sequencing was used to compare bacterial communities in soils from swamp meadows (SM), alpine meadows (AM), alpine steppes (AS), and desert steppes (DS) at the eastern edge of the Qinghai–Tibetan Plateau (QTP) in China. We then compared response to nitrogen addition between SM and DS soils in microcosms. Bacterial α-diversity decreased from SM > AM > AS > DS. Variations in soil properties across grassland types was associated with different soil bacterial communities corresponding to bacterial species associated with nutrient cycles to those associated with degradation. Soil moisture, pH, and total phosphorus were the main drivers of these differences. Nitrogen addition decreased bacterial diversity but had inconsistent effects on soil bacterial communities in SM and DS, which may also indicate that different alpine grassland soil types have unique bacterial communities. Alpine grassland degradation significantly affects bacterial communities, and the response to nitrogen addition depends on the alpine grassland type. These results allow for better predictions of soil bacteria community-level responses to geochemical and environmental change in alpine areas.